Everyday secrecy: boundaries of confidential gossip. Issue 3 (4th May 2021) - Fan, Ziyun; Grey, Christopher
ABSTRACT: Gossip is an everyday part of organizational life and has been increasingly researched. However, some gossip has a particular character, whereby it is to some degree secret. Drawing on studies of both gossip and secrecy, in this paper we explore this 'confidential gossip' via a participant observation case study. This was based on an internship with Quinza, a British media company, and had a covert element which is discussed and justified. Specifically, we show how the boundaries around confidential gossip are marked in organizational interactions. The paper contributes to existing knowledge about organizational gossip by showing the particular significance of secrecy which makes confidential gossip a more potent source of group inclusion and exclusion.